The Digital Banking Services: A Selection Model from Islamic Banks - Hidayat, Achmad; Kassim, Salina (UUM Press, 2023)
The digital banking services which consist of internet banking and mobile banking have occupied an important role in the financial sector. Despite the importance of digital banking, Islamic banks in Indonesia have encountered issues with the adoption of digital banking such as budget constraints as well as sizable investment. Therefore, it is important to examine how to prioritize the selection of digital banking services in Islamic banking. This study aims to propose a model for prioritizing the selection of digital banking services in Islamic banking by applying document research through analyze way the paper or journals and other published sources concerning with the digital banking and product development in Islamic banking. While most of the studies conducted in the conventional banking, in this study the proposed model is built to address the Islamic banking. The proposed model comprises six criteria and six alternatives of services that should be considered in the selection of digital banking services from Islamic banks perspective. The proposed model involves general criteria that presence in the general banking context (conventional banking or Islamic banking) and specification criteria which only presence in the Islamic banking namely Sharia (Al-Syari’ah). Therefore, the proposed model has characterized the model utilized for the Islamic Bank in prioritizing the services in digital banking.